Study On Strength Of Geopolymer Concrete - Navyashree B R,Ganesha Mogaveera (International Journal of Advanced Science and Technology, 2020)
In this research, study has been conducted about strength parameters on geopolymer concrete and the results are compared with the strength properties of conventional concrete of M30 grade. Combination of Sodium Hydroxide and Sodium Silicate are used as alkaline solution with the ratio of 2.5 and molarity 12M. The investigation resulted that there is increase in strength with increase in fly-ash percentage rather than increment in GGBS percentage in concrete. When compared with conventional concrete, the strength gained is more in Fly Ash-GGBS based geopolymer concrete.